Building resilience to urban food insecurity in Bulawayo City, Zimbabwe - Dube, Thulani (Stellenbosch : Stellenbosch University, 2025)
ENGLISH ABSTRACT: Given the rapid rate of urbanisation in Africa, food insecurity, once predominantly encountered in rural areas, is now increasingly manifesting in urban areas. Despite this, food security programming generally remains focused on rural productionist approaches ill-suited for urban contexts. This suggests that urban food insecurity remains largely misunderstood, bringing into question the effectiveness of resilience-building programmes and strategies being adopted to address it. Focusing on the city of Bulawayo in Zimbabwe, this study aimed to determine the nature and effectiveness of food security resilience-building strategies currently being employed there by a range of different stakeholders, from the state, Non-Governmental Organisations (NGOs) and United Nations Agencies to the beneficiary households themselves. In achieving this aim, the objectives of this study were to identify the common shocks to the urban food system in Bulawayo, document the current resilience building strategies being used by different stakeholders, assess the effectiveness of those strategies in addressing food insecurity among poor urban households, and to proffer recommendations about how resilience building programming in Bulawayo and other urban areas might be improved. The study utilised a mixed methods research approach. These included the collection of both quantitative and qualitative data employing a survey questionnaire targeting 200 food insecure beneficiary households, focus group discussions with representatives of food insecure households, and key informant interviews with various stakeholders, including the Bulawayo city council administrators, NGO managers and government officials. The data was then analysed using Microsoft Excel for survey data and thematic analysis for qualitative data from interviews and focus group discussions. The main risk driver of food insecurity in Bulawayo was found to be related to the deteriorating broader macro-economic environment in Zimbabwe, which is resulting in high unemployment, hyper-inflation and low incomes in general. The study also established that climate change impacts and the recent Covid-19 pandemic had deepened food insecurity. In response, the strategies being implemented to build food security resilience were the promotion of urban agriculture, cash transfer programs, casual work and income-generating projects. The study then questioned to what extent these and other interventions really were building “resilience”, given the range of constraining factors revealed. The thesis concludes by making recommendations about how these might be addressed.